Immunological status in acute pneumonia in children under 2 years old with atopic dermatitis: A parallel group clinical trial. - Sadikov, N.I.; Aliyev, A.L.; Kuziyev, D.V.; Akhrorkhonov, R.A. (European Journal of Pediatric Dermatology, 2023)
Background. Atopic dermatitis (AD) is a chronic skin disorder that affects children worldwide. AD children have an increased risk of developing asthma and other allergic diseases. Acute pneumonia is a respiratory infection that can cause significant morbidity and mortality, especially in children under 2 years old. However, it is not clear how the immune system responds to acute pneumonia in AD children under 2 years old. Objective. This study aimed to investigate the immune response of children under 2 years old with AD who develop acute pneumonia and compare it with children without AD who develop acute pneumonia. Materials and Methods. The study included children under 2 years old hospitalized with a diagnosis of acute pneumonia. Participants were divided into two groups: Group A included children with AD who developed acute pneumonia, and Group B included children without AD who developed the same infection. Results. The study included 50 children, 25 in each group. Group A had significantly higher levels of IL-4, IL-5, and IL-6 on admission to the hospital compared to Group B. Children with AD had a longer hospital stay and required oxygen therapy more frequently. Conclusion. Children under 2 years old with AD who develop acute pneumonia have a different immune response compared to those without AD. They also have a longer hospital stay and are more likely to require oxygen therapy.